Insight into tropical cyclone behaviour through examining maritime disasters over the past 1000 years based on the dynastic histories of China – A dedication to Ocean Researcher V. (8th June 2017) - Liu, Yen-Chu; Chen, Huei-Fen; Liu, Xingqi; Chang, Yuan-Pin
Abstract: This paper uses China's historical records to gather information on maritime disasters caused by tropical cyclones. Official records show that there were a total of thirteen major maritime disasters possibly caused by tropical cyclones. Maritime disaster variation trends indicate that tropical cyclones tend to strike the southern coast of China during a La Niña-like stage whereas an El Niño-like stage leads to tropical cyclones being guided northward toward the Korean Peninsula and Japan. During China's Yuan Dynasty (AD 1271–1368) Kublai Khan tried to invade Japan twice during an El Niño-like stage and encountered intense tropical cyclones, which the Japanese called Kamikaze . During a La Niña-like stage, multiple maritime disasters occurred in the East China Sea, the Taiwan Strait and the South China Sea in the Qing Dynasty (AD 1636–1912). Indeed, the historical record of the Qing Dynasty details maritime disasters at least 9 times. These events were also caused by tropical cyclones. In addition, statistics on the seasons of tropical cyclone genesis and their landfall locations from AD 1945–2013 in the Northwest Pacific Ocean region reveal that in summer, tropical cyclones tend to make landfall along coastal regions north of Fujian Province, eastern China; however, in autumn and winter, cyclones tend to be guided further southward to make landfall in southern China (Hainan), Vietnam, and the Philippines. This phenomenon in seasonal variation is reflected in the maritime disaster events recorded for coastal regions of southeastern China and landfall locations of tropical cyclones during the Qing Dynasty.